Impacto del Bullying en la autoimagen corporal de los estudiantes de Educación Básica Superior de la Unidad Educativa Eugenio Espejo, del cantón Babahoyo - Martínez Obando, María Adela (2025)
Bullying is a problem that affects the emotional and academic development of students. This study focused on investigating its impact on the body self-image of students in Higher Basic Education at the Eugenio Espejo Educational Unit in Babahoyo. The general objective was to determine the relationship between bullying and body perception, establishing the prevalent types of bullying and evaluating the levels of body dissatisfaction. Methodologically, a mixed approach was used: quantitative surveys (BSQ and OBQ) to measure the prevalence of bullying and the degree of body dissatisfaction, and qualitative interviews with the psychological team, which allowed to delve into the personal experiences of the students. The results showed that verbal and psychological bullying were the most common forms, generating avoidance behaviors, low self-esteem and marked body dissatisfaction in the victims. Likewise, a significant impact on academic performance and emotional well-being was detected, corroborating previous findings that point to the need for timely interventions. Among the conclusions, the relevance of promoting an inclusive and safe school climate, where families and teachers work together to prevent bullying and strengthen the self-esteem of young people was highlighted. The study recommends the implementation of prevention and support strategies, including awareness workshops and early detection protocols. These measures not only address the bullying itself, but also have a direct impact on the comprehensive education of students. Thus, student mental health and development are protected.